Influence of mesoscale eddies on the cross-shelf phosphate transport of the Kuroshio Current northeast of Taiwan: A modeling study - Xu, Lingjing; Yang, Dezhou; Feng, Xingru; Sun, Junchuan; Gao, Guandong; Cui, Xuan; Yin, Baoshu (Frontiers in Marine Science, 2023)
The Kuroshio Current flows northeastward along the East China Sea (ECS) shelf break, carrying a large amount of nutrients, and is thus an important source of nutrients for the ECS. The mainstream and transport of the Kuroshio Current are significantly affected by mesoscale eddies. However, the influence of mesoscale eddies on the Kuroshio nutrient input into the ECS is unknown. We add constructed cyclonic and anticyclonic eddies to a hydrodynamic model to explore the influence of mesoscale eddies on cross-shelf Kuroshio phosphate input into the ECS. This model suitably reproduces the fate of mesoscale eddies and the variation in the Kuroshio Current during eddy-current interactions. The simulation results reveal that during the strong interaction between the Kuroshio Current and mesoscale eddy east of Taiwan, the cyclonic eddy reduces the on-shelf phosphate flux, while the anticyclonic eddy increases the Kuroshio phosphate input to the ECS. When the anticyclonic eddy moves to the Okinawa Trough, it reduces the Kuroshio phosphate input into the ECS.These basic features are not sensitive to the initial latitude of the eddy center east of Taiwan. The change in cross-shelf phosphate flux is caused by the changes in cross-shelf velocity and phosphate concentration along the shelf. Momentum balance analyses suggest that the change in cross-shelf velocity is mainly caused by the change in the pressure gradient term due to eddy-induced changes in sea surface height in the horizontal direction and isotherm tilting in the vertical direction. The advection-diffusion equation analysis shows that the change in phosphate concentration along the shelf is attributed to changes in the upper horizontal advection and lower vertical advection of phosphate, which are induced by the upper phosphate change and vertical velocity change along the shelf, respectively. This study has important implications for the possible response of the ECS ecosystem to mesoscale eddies that are partly triggered by enhanced typhoons east of Taiwan under global warming.